Neighbourhood Selection of Non-Western Ethnic Minorities: Testing the Own-Group Preference Hypothesis Using a Conditional Logit Model - Sanne Boschman; Maarten van Ham (Institute for the Study of Labor (IZA), 2013)
The selective inflow and outflow of residents by ethnicity is the main mechanism behind ethnic residential segregation. Many studies have found that ethnic minorities are more likely than others to move to ethnic minority concentration neighbourhoods. An important question which remains largely unanswered is to what extent this can be explained by own group preferences, or by other neighbourhood or housing market factors. By using longitudinal register data from the Netherlands, this study contributes to the literature on neighbourhood selection by ethnic minorities in two ways. First, it distinguishes between different ethnic minority groups where most studies look at the group as a whole. Second, it takes into account multiple dimensions of neighbourhoods where most other studies look at neighbourhoods one-dimensionally, which allows us to test the own group preferences hypothesis. Using a conditional logit model we find that housing market constraints can partly explain the selection of ethnic minorities into minority concentration neighbourhoods. Also own-group preferences are found to be important in explaining neighbourhood selection. There are, however, differences between ethnic minority groups. Own-group preferences and housing market constraints together explain why Surinamese and Antilleans select into minority concentration neighbourhoods. When these factors are taken into account, Turks and Moroccans are still found to select into concentration neighbourhoods of ethnic minorities other than their own ethnic group.
Keywords: J15; R23; 330; segregation; neighbourhood selection; ethnicity; own-group preference; conditional logit; the Netherlands